Typology of Chinese Languages (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
While often perceived as a single language, “Chinese” is, in fact, a diverse branch of the Sino-Tibetan family, with internal variation comparable to that of the Romance or Germanic languages. This Special Issue, “Typology of Chinese Languages: One Name, Many Languages”, examines this complexity by challenging monolithic views and showcasing the rich tapestry of Sinitic diversity. The contributions move beyond well-known standardized languages to analyse lesser-known contact varieties, transitional dialects, and innovative grammatical constructions—from the Russian-influenced Dungan in Central Asia to the complex verb systems of Cantonese and the modal expressions of Wu dialects. Using historical, quantitative, experimental, and descriptive methods, the papers investigate phonology, morphosyntax, and the lexicon, analysing everything from dative markers and causative constructions to tonal behaviour and the function of classifiers. This volume offers a crucial, data-rich update to the field, providing a nuanced perspective on the dynamic interplay of inheritance, contact, and evolution that defines Sinitic typology today.